THE VALUES EDUCATION CHILDREN’S OF PERSPECTIVE THE KORAN (Stories Tafsir The Koran Surah Ibrahim Chapter 35-36 and Surah Yusuf Chapter 5) - Julina Saputri Siregar, Syamsu Nahar, Zulheddi (Pascasarjana UIN Sumatera Utara, 2019)
Abstract: This study aims to analyze: 1) How are the commentators of the scholars about surahIbrahim ayat 35-36 dan surah Yusuf 5? 2) What are the values of children’s education contained in theQur’anic surah Ibrahim and surah Yusuf? and 3) What is the relevance of the values of children’seducation in Surah Ibrahim and Yusuf at the present time with the future?. This study uses a qualitativemethod, using the Tafsir approach to interpretation, which uses the primary source is the Koran. Amongthe commentaries used are tafsir al-Marâgi by Ahmad bin Musthafâ al-Marâgi, Ibn Katsir’s tafsîr byMuhammad, the fate of Ar-Rifa’i. The results showed that: 1) Explanation of how the interpretation ofthe scholars about children’s education in the Qur’an Ibrahim and Surah Yusuf surah, is: Islamic educationcan form a person who is capable of realizing divine justice in the human community and is able toutilize natural potential by using fair. 2) There are four values of Islamic education in the surah Ibrahimand surah Yususf in the Qur’an, are: the values of aqeedah, values of leadership, values of worshipand moral values. 3) The relevance of the values of children’s education in the surah Ibrahim andSurah Yusuf that occur in the present condition of society, namely decadation of morals, morals andhubbuds of dunyâ. This condition is reflected in the values of Islamic education in the study of Ibrahimand Surah Yusuf in the Qur’an that the values of Islamic education in the study of Surah Ibrahim andSurah Yusuf in the Qur’an can change human moral conditions for the better guided by the Koran andHadith, enhance noble attitudes, behave well, believe in themselves, foster tolerance, and possess qana’ah.Keywords: Values Education, Children’s, Koran